Kebijakan Hukum Pidana Pencurian dengan Pemberatan dan Pencurian Kekerasan - Rizki Firmanda Dardin; Mhd. Akbar (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Based on the available data, theft is one of the most frequently committed criminal offenses, and many theft cases remain unresolved. As a law enforcement institution, the police are required to carry out their duties in accordance with their legal authority, including enforcing the law against criminal offenses, particularly aggravated theft. This study aims to examine the implementation of criminal investigations into aggravated theft within the jurisdiction of the Medan City Police Department (Polres Medan). It also seeks to identify the challenges encountered by investigators during the investigation of aggravated theft cases. This research employs an empirical normative legal research method using both statutory and case approaches. The research data consist of primary data obtained through interviews and secondary data derived from primary legal materials, including the Indonesian Criminal Code (KUHP), the Indonesian Code of Criminal Procedure (KUHAP), and Law No. 2 of 2002 on the Indonesian National Police, as well as secondary legal materials such as books and scholarly journals. Data were collected through interviews and literature review and analyzed using a deductive approach. The findings indicate that the investigation of aggravated theft cases conducted by the Medan City Police Department has been carried out in accordance with the provisions of Law No. 8 of 1981 concerning the Indonesian Code of Criminal Procedure (KUHAP). However, several obstacles were identified during the investigative process, including the disproportionate number of cases compared to the number of investigators, requiring investigators to handle multiple cases simultaneously.